The effects of self-directed learning based on video prompting in improving 27 daily living skills for adolescents with mild intellectual disability in China - Li, Huan; Yao, Shijie; Luo, Yueling; Guo, Congyun; Bian, Huimin; Peng, Jie; Wu, Yuke; Chen, Wenchai (Research in developmental disabilities, 2025)
Students with intellectual disability often face challenges in mastering daily living skills. Existing intervention strategies for these skills typically require support from instructors, which limits the autonomy and independence of these students. Consequently, this study aims to develop a self-directed learning approach based on video prompting to enhance the daily living skills of students with mild intellectual disability. The research employed a multiple probe across behaviors design to evaluate the effectiveness of this approach among three adolescents with mild intellectual disability in China, focusing on 27 daily living skills across three categories: cooking, cleaning, and household appliance usage. Additionally, six skills were randomly selected to assess the generalization effects of acquired skills to real-life scenarios. All three participants acquired 27 skills within 27 intervention sessions, achieving average task completion accuracy of 98 %, 94 %, and 96 % across three categories of skills. Participants also demonstrated improved self-correction accuracy during the self-directed learning process. Furthermore, they successfully generalized all selected skills to real-life family scenarios. These results support the high efficiency and effectiveness of the self-directed learning approach. These preliminary findings underscore the potential of self-directed learning in empowering individuals with mild intellectual disability toward greater independence and lifelong skill acquisition. Future research should explore the broader applicability of this learning approach. •Introduction of a novel self-directed learning approach to enhance daily living skills in adolescents with mild intellectual disabilities.•Introduction of self-correction accuracy to measure error-correction abilities during self-directed learning.•Improved intervention efficiency by enhancing 27 essential skills across three domains within just 27 sessions.•Successful generalization of acquired skills to real-life family situations.